Health Manpower Planning Process. Health Planning Methods and Technology Series. Number 1 - Aspen Systems Corp., Germantown, MD.; Aspen Systems Corp., Germantown, MD. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This monograph, the first of a series of monographs for health planners, focuses on both State and area-wide health manpower planning. Content is presented in four chapters: Chapter I briefly provides background information about the monograph. Chapter II presents the concepts used and the setting within which they are applied. Chapter III describes the basic components of the health manpower planning process and the inputs necessary to initiate and sustain it, and chapter IV details six steps required for plan development. Two appendixes are included which review the steps in planning and describe selected strategies used by health planners to maximize their available resources. (WL)
Sponsoring Agency: Health Resources Administration (DHEW/PHS), Bethesda, MD. Bureau of Health Resources Development.
Sponsoring Agency: National Health Planning Information Center (DHEW/PHS), Rockville, MD.
Contract Number: HRA-230-75-00073.
ERIC Note: Charts may be marginally legible due to small print of original document.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conceptual Schemes; Health Personnel; Labor Needs; Organization; Program Development; Staff Utilization; Statewide Planning; Systems Concepts; Books